Pengaruh Diet Gluten-Free Casein-Free (GFCF) terhadap Gejala Perilaku pada Anak dengan Autism Spectrum Disorder (ASD): Literature Review - Rosellini, Rayna; Rasendriya, Edwin (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by impairments in social interaction, communication difficulties, and restricted and repetitive behaviors. In addition to these core symptoms, children with ASD often experience gastrointestinal disturbances that are thought to be related to the gut–brain axis. One non-pharmacological intervention that has been widely studied to reduce ASD symptoms is the gluten-free casein-free (GFCF) diet. However, evidence regarding its effectiveness in improving behavioral symptoms remains inconsistent. This study aims to review previous research on the impact of gluten and casein consumption on behavioral symptoms in children with ASD using a narrative literature review approach. Literature searches were conducted in PubMed, ScienceDirect, and Google Scholar for articles published between 2014 and 2024 using the keywords Autism Spectrum Disorder (ASD), behavior, GFCF diet, gluten, and casein. The review results indicate that most studies report potential benefits of the GFCF diet in improving certain behavioral symptoms in children with ASD, particularly hyperactivity, behavioral problems, stereotypical behavior, attention, and cognitive function. Some studies also show improvements in autism evaluation scores after dietary implementation over a specific period. However, findings remain inconsistent due to differences in study design, sample size, intervention duration, dietary adherence, and the heterogeneity of ASD characteristics among children. In conclusion, the GFCF diet has potential as a complementary intervention to improve certain behavioral symptoms in children with ASD, but further high-quality studies with larger samples are needed to confirm its effectiveness more consistently.